2016
DOI: 10.13005/bbra/2126
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Efficacy of HEART Score in Prediction of Major Advanced Cardiac Events in Patients with Chest Pain

Abstract: Chest pain is one of the most common reasons for admitting patients to the emergency room. The focus of the diagnostic process in chest pain patients at the emergency department is to identify both low and high risk patients for an acute coronary syndrome (ACS). Numerous risk prediction scores have been developed for fast and accurate risk stratification of chest pain in ED, like HEART score that a new ED Chest Pain risk stratification score. In this prospective cohort study, we aimed to evaluate efficacy of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Our search identified 778 citations (Figure ) and following removal of duplicates, we screened 557 studies, from which 62 studies underwent full‐text review. We included 29 distinct cohorts from 30 studies in the meta‐analysis . All included studies evaluated the prognostic accuracy of the HEART score using a low‐risk threshold (score between 0 and 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our search identified 778 citations (Figure ) and following removal of duplicates, we screened 557 studies, from which 62 studies underwent full‐text review. We included 29 distinct cohorts from 30 studies in the meta‐analysis . All included studies evaluated the prognostic accuracy of the HEART score using a low‐risk threshold (score between 0 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…There were 17 (56.7%) retrospective cohorts, 11 (36.7%) prospective cohorts, and two (6.7%) randomized trials. Sixteen studies evaluated the HEART score for 30‐day incidence of MACE, while 13 evaluated the HEART score for 6‐week incidence of MACE . Most studies included only patients presenting with chest pain, while five studies included patients presenting with “suspected ACS.” In 14 studies, the ECG was interpreted by an ED physician, while in seven studies the ECG was specifically interpreted by a cardiologist .…”
Section: Resultsmentioning
confidence: 99%
“…Backus et al in 2013, estimated a HEART score of 6.54 in positive MACE, while the score was 3.96 in negative MACE (19). In Bolvardi et al study, a similar result was observed: 7.42 in positive MACE and 5.42 in negative MACE (2).…”
Section: Study Population=200mentioning
confidence: 74%
“…Clinicians can decide whether to release and discharge patients or admit them for further evaluations (16). In previous studies, it is reported that there is a significant difference in the predictive value of HEART score comparing to other scoring tools (2,15). Literature still needs more research in this field to estimate the exact value of HEART score in patients' disposition in ED.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation